1970
DOI: 10.3329/jbcps.v28i3.6508
|View full text |Cite
|
Sign up to set email alerts
|

Student's Opinion Towards the Assessment System of Revised Undergraduate Medical Curriculum - An Experience in A Private Medical College

Abstract: Objectives: The aim of the study was to assess the attitude of the undergraduate medical students towards the assessment system of revised medical curriculum. Procedure: During the placement of the students in the department of Obstetrics and Gynaecology, the basic idea of the old and the new curriculum was explained to them. The objective of the study was explained and a pretested questionnaire was given to each student. Identification of the student was not compulsory to maintain secrecy. 5 point Likert scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

1970
1970
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…Evaluation of teaching curriculum by students is firmly recommended as a part of teaching -learning process 10 and has been attempted by a number of educational researchers. Most of the previous studies revealed overall satisfactory opinions regarding revised MBBS curriculum which differs from this study where majority (94%) has recommended a number of changes [11][12][13][14] . However these shared similar responses in few points as-increasing course duration 11,13 , community oriented trainings 12 , revising frequency of professional exams per year 11 , and rearranging block posting 14 , etc.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…Evaluation of teaching curriculum by students is firmly recommended as a part of teaching -learning process 10 and has been attempted by a number of educational researchers. Most of the previous studies revealed overall satisfactory opinions regarding revised MBBS curriculum which differs from this study where majority (94%) has recommended a number of changes [11][12][13][14] . However these shared similar responses in few points as-increasing course duration 11,13 , community oriented trainings 12 , revising frequency of professional exams per year 11 , and rearranging block posting 14 , etc.…”
Section: Discussioncontrasting
confidence: 66%
“…Regarding MBBS course content versus duration, majority of the respondents gave a positive opinion as in studies done earlier 12,13 where a few voted for content reduction 11 . Besides, 85% of the participants were satisfied with all the components of current assessment system where the rest showed different opinions like-balancing MCQ contents with SAQs, remodeling oral and practical assessment tools and exam schedules 11,15 .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations